Non-Verb al Communication in the Early Days of the American Conquest - Jáimez Esteves, Rita (2014)
Over the centuries, mankind tried to communicate with each other in all circumstances of life, and although there is not a common language shared by all members of the world, there is a constant flowing of information. In order to illustrate this perspective, let us take into account Christopher Columbus arrival to America, in which two languages collide. Neither foreigners nor native knew the language they were hearing; however, they dialogued. The following work presents how signs, illustrations and their interpreters allowed communication in the first days of the American conquest. It also revises several chronicles, mainly in the Antilles and Venezuela, based on Christopher Columbus’ Diary and Galeotto Cey’s (1539-1553) Viaje y descripción de las Indias.